Comparison of volar and dorsal plate osteosynthesis for radial shaft fractures: an anatomical pilot study. (November 2017) - Holweg, Patrick; Hohenberger, Gloria M.; Schwarz, Angelika M.; Staresinic, Mario; Krassnig, Renate; Grechenig, Stephan
Abstract: Background: No publication has yet described the interface between the radius and the plate in various positions. Neither clinical examination nor assessment of fracture radiographs provides information about the anatomy of the radius before injury. Purpose: We investigated radius anatomy to analyse dorsal and volar plate-to-bone fit for radial shaft fracture management. Methods: We examined 20 specimens from human adult cadavers. An 8-hole 3.5-mm titanium locking plate was used at three different positions on the dorsal and the volar side of the bone. The space between the well-positioned plate and the radial shaft was attained for each hole of the plate. Results: The average space between the midshaft radial cortex and the plate holes for all positions was 0.69 mm (range: 0.0 mmto 2.38 mm). The greatest mean distance between the plate and the radial cortex was measured at the volar mid-diaphyseal position of the plate with an average of 1.31 mm. Conclusion: This incongruence between the radial cortex at the volar diaphysis and the plate should be considered when applying plates to this position of the radius. The results of this cadaver study indicate that radius plate osteosynthesis should preferably be done from the dorsal side.